Book Reviews - Judy Halden-Sullivan; Ken DeLucca; Brad Lucas; Timothy Shea; William Archibald (Journal of the Assembly for Expanded Perspectives on Learning, 2010)
Book Reviews Judy Halden-Sullivan - Practices in Mindfulness Ken DeLucca - Schoeberlein, Deborah and Suki Sheth. Mindful Teaching and Teaching Mindfulness: A Guide for Anyone Who Teaches Anything. Boston: Wisdom Publications, 2009. Brad Lucas - MacDonald, Elizabeth, and Dennis Shirley. The Mindful Teacher. New York: Teachers College Press, 2009. Timothy Shea - VanDeWeghe, Richard. Engaged Learning. Thousand Oaks, CA: Corwin, 2009. William Archibald - Cummings, Robert E. Lazy Virtues: Teaching Writing in the Age of Wikipedia. Nashville, TN: Vanderbilt UP, 2009